Emerging Economies: Equity and Debt Market - Shah, Amisha (2009)
This dissertation provides evidence to support the hypothesis that suggests the investment in emerging markets and the valuation of the emerging equity and debt markets. It examines the close relationship between emerging and developed global markets.